THE SCIENTIFIC HERITAGE OF THE SCIENTISTS WHO LIVED IN CHAGANIYAN IN IX-X CENTURIES - Ergashev Mavlon Eshniyozovich (Journal of Learning on History and Social Sciences, 2024)
In the 9th-10th centuries, Chaganion became one of the major cultural centers of Central Asia. Along with the socio-economic development of the country, this was caused by the great care of Chaganiyan emirs for the development of science and culture.